Bioresources: Back to the Ancient World? - Katouzian-Safadi, Mehrnaz; Merlet, Lea; Marchand, Patrice A. (International Journal of Bio-resource and Stress Management, 2021)
With the increase rejection of synthetic chemistry, recourse to natural substances is privileged in the biocide and plant protection sectors. Indeed, various voices are raised and demand that plants be treated other than with pesticides and chemical fertilizers. Many people want to quickly expand the range of herbal treatments based on “natural” products. Therefore, Bioresources are naturally called upon to help with this demand from civil society. Does this mean going back to ancient times?